2015
DOI: 10.5539/ies.v8n5p119
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Pre-service English as a Foreign Language Teachers’ Technological Pedagogical Content Knowledge

Abstract: The present research aimed to assess pre-service English as a foreign language teachers' technological pedagogical content knowledge. A total of 76 undergraduate students enrolled in an English language teaching (ELT) program at a major state university in Turkey were recruited in the study and were asked to anonymously complete the Technological Pedagogical Content Knowledge Scale and answered some open-ended questions. The findings revealed a highly developed knowledge of TPACK (Mean > 3.5; 81%). Gender diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 15 publications
3
17
1
3
Order By: Relevance
“…The analysis of the findings suggested that the participants in this study had a high level of TPACK. This in line with the literature which usually indicated that pre-service teachers had a high level of TPACK (Kabakçı Yurdakul, 2011;İşigüzel, 2014;Öz, 2015;Şimşek et al, 2013) while there are few others who suggested that the participants had a medium level of TPACK (Argon et al, 2015). The difference in Argon et al (2013) may stem from the difference in the participants.…”
Section: What Is the Level Of The Participants' Tpack?supporting
confidence: 87%
“…The analysis of the findings suggested that the participants in this study had a high level of TPACK. This in line with the literature which usually indicated that pre-service teachers had a high level of TPACK (Kabakçı Yurdakul, 2011;İşigüzel, 2014;Öz, 2015;Şimşek et al, 2013) while there are few others who suggested that the participants had a medium level of TPACK (Argon et al, 2015). The difference in Argon et al (2013) may stem from the difference in the participants.…”
Section: What Is the Level Of The Participants' Tpack?supporting
confidence: 87%
“…One explanation might be that a majority of students in our study were at the beginning of the second academic year and this result corresponds to a previous study in Estonia (Luik et al, 2018), in which pedagogical knowledge was assessed to be the lowest. Similarly, our results, that content knowledge was assessed lower by EYT students, have also been confirmed in several previous studies (Dong et al, 2015;Koh et al, 2010;Öz, 2015).…”
Section: Resultssupporting
confidence: 92%
“…Arvestades, et enamik meie uuringus osa lenud KELA üliõpilastest oli läbinud aasta õpetaja-koolituses, olles teise õppeaasta alguses, siis on ka see tulemus ootuspärane ning vastab Eestis tehtud varasema uuringu tulemustele, mille kohaselt hinnati pedagoogikateadmisi kõige madalamaks (Luik et al, 2018). Seda, et üliõpilased hindavad aineteadmisi mada lamaks, on leitud ka mitmes varasemas uuringus (Chai et al, 2011;Dong et al, 2015;Koh et al, 2010;Öz, 2015).…”
Section: Aruteluunclassified
“…The statistical results suggested a higher increase in female pre-service English language teachers' post test results when compared with the males. Studies (Öz, 2015;Solak & Çakır, 2014) revealed a significant difference in favor of males in terms of technological knowledge. On the other hand, females in these studies scored higher than males in pedagogical knowledges.…”
Section: Resultsmentioning
confidence: 99%